Blockchain-enabled Clinical Study Consent Management - Jung, Hans H.; Pfister, Franz M.J. (Technology innovation management review, 2020)
Written informed consent (WIC) is required in the context of voluntary participation in a clinical trial. The trial participant gives WIC in accordance with various regulatory requirements. We present a framework concept for a blockchain-based distributed ledger solution, which aims at implementing simple and secure management of WIC documentation, along the entire data value chain from acquiring consent to academic publication, and (commercially) exploiting the results of a clinical study. This may include (but is not limited to) clinical deployment, security monitoring, and conformity with data privacy and ethical standards. Thus, we present a potential "Health AI" application that goes beyond WIC documentation, to enabling the creation of a holistic data provenance trail graph. Such a framework concept aims to create sustainable value for study participants, clinicians, data scientists, and ultimately consumers. The framework's usefulness is relevant for ensuring the ethical development of artificial intelligence applications in the healthcare domain.